Pengaruh Kompetensi, Motivasi, dan Gaya Kepemimpinan Terhadap Kinerja Pegawai pada Kantor Pelayanan Pajak Pratama Makassar Selatan - Fadli Fadli (STIM LASHARAN JAYA MAKASSAR, 2018)
The purpose of this study is to determine the Influence of competence, motivation, and leadership style on employee performance at Tax Office Pratama South Makassar consisting of Competence, Motivation, and Leadership Style. The population in this study is employees At Tax Office Pratama South Makassar with the number of samples of 84 people. Methods in collecting data in this study are questionnaires, interviews, and documentation. The method of data analysis using descriptive method and quantitative method is by multiple linear regression analysis used to measure Influence of competence, motivation, and leadership style on employee performance at Tax Office Pratama South Makassar. Based on the F test of independent variables (competence, motivation, and leadership style) together have a positive and significant effect on the dependent variable (employee performance). Through testing the correlation coefficient (R) obtained that the level of correlation or the relationship between competence, motivation, and leadership style of employee performance has a high relationship that is 98,2%. And leadership style is the most dominant factor affecting employee performance at Tax Office Pratama South Makassar.